Do as the Swedes do? Internet policy and regulation in Sweden – a snapshot - Merlin Münch (Internet Policy Review, 2013)
When it comes to information technology Sweden is considered to be at the forefront both in terms of technological innovation, as well as in progressive policy-making, regulation and internet freedom. This article investigates the state-of-affairs in a number of fields of Swedish internet policy, such as copyright, net neutrality and censorship, in order to find out if and why the 'Swedish way' has been particularly efficient. In the course of this article it will become apparent that Swedens approach to internet policy and regulation has often been controversial, as the examples of the contested National Defence Radio Establishment law (known as the 'FRA-law'), as well as the rigorous implementation of the Directive on the enforcement of intellectual property rights have shown. Also, when it comes to matters of transparency, the Swedish government has some catching up to do.
Keywords: 300; Sweden; Surveillance; Copyright; E-government; Internet policy